Spatial and temporal patterns in the hyperbenthic community structure in a permanently open Eastern Cape estuary, South Africa - Heyns, Elodie R (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2010)
The spatial and temporal (seasonal and diel) patterns in the hyperbenthic community structure (>500 μm) was investigated in the warm temperate, permanently open Kariega Estuary situated along the south-eastern coastline of South Africa. Spatial and seasonal patterns in the hyperbenthic community structure were assessed monthly at six stations along the length of the estuary over a period of twelve months. Data were collected using a modified hyperbenthic sledge, comprising two super-imposed nets. Physico-chemical data indicate the presence of a constant reverse salinity gradient, with highest salinities measured in the upper reaches and lowest at the mouth of the estuary. Strong seasonal patterns in temperature, dissolved oxygen and total chlorophyll-a (chl-a) concentrations were evident. Total average hyperbenthic densities ranged between 0.04 and 166 ind.m-3 in the lower net and between 0.12 and 225 ind.m-3 in the upper net. Hyperbenthic biomass values ranged between 0.02 and 11.9 mg.dry weight.m-3 in the lower net and between 0.02 and 17.4 mg.dry weight.m-3 in the upper net. A spatial and temporal pattern in total densities was detected with an increase in abundance over the period of September to October 2008 particularly in the middle reaches (Stations 3 and 4). Both the lower and upper nets were numerically dominated by decapods (mainly brachyuran crab zoeae) with the exception of June and July 2008 when mysids (mainly Mesopodopsis wooldridgei) dominated, making up 72.4 ± 58.14% of the total abundance in the lower net. A redundancy analysis (RDA) indicated that 99.2% of the variance in the hyperbenthic community structure could be explained by the first two canonical axes. Axis one, which accounted for 96.8% of the total variation detected in the ordination plot was highly correlated with sedimentary organic content and to a lesser extent the chl-a concentration within the Kariega Estuary. The correlations with the second canonical axis (2.4%) were less obvious, however, salinity and seston concentration were weakly correlated with this axis. Diel variability in the hyperbenthic community structure was assessed during March 2009. Samples were collected during the day and night (n = 6 for each period) using sampling gear described above. Total average hyperbenthic densities during the day (497.9 ± 254.1 ind.m-3) were significantly higher than night-time estimates (129.9 ± 38.5 ind.m-3; p<0.05). There were no significant differences in the average dayand night-time estimates of hyperbenthic biomass (p>0.05). A hierarchical cluster analysis identified two significantly distinct groupings, designated the day and night samples. Results from the SIMPER procedure indicated that the high densities of crab zoeae recorded during the day-time accounted for the majority of the dissimilarity between the day and night groupings (44.7%). In addition, it is apparent that several benthic species, especially from the cumacean and isopod orders, were absent from the hyperbenthos during the day-time and emerged into the water column at night.
Keywords: Sundays Estuary -- South Africa -- Eastern Cape; Groundfishes -- South Africa -- Eatern Cape; Estuaries -- South Africa -- Eastern Cape